The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/su11040964
|View full text |Cite
|
Sign up to set email alerts
|

A Strategic Approach to Sustainable Tourism Development Using the A’WOT Hybrid Method: A Case Study of Zonguldak, Turkey

Abstract: Nowadays, tourism-led economic growth has become a major outcome of the public policy. Researchers have recently begun to address the development of tourism from a perspective that is based on economic, cultural, social, and environmental sustainability. This paper aims at presenting a strategic approach that can help to develop sustainable tourism at touristic destinations. In order to pursue our aim, the A’WOT (AHP-SWOT) hybrid method, developed in combination with SWOT (Strengths, Weaknesses, Opportunities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 69 publications
(92 reference statements)
0
93
0
17
Order By: Relevance
“…Based on this gap in the literature, the aim of the study is to examine the relationship between GMO and environmental and social performance of the firm in the context of the hospitality sector. This study is significant as the tourism industry is slowly changing priorities from pure economic considerations to a sustainable tourism marketing model (Aimagambetov, et al, 2017;Kisi, 2019). This study will make an empirical contribution to the literature on the nexus between GMO and environmental and social performance in the context of the hospitality industry.…”
Section: Introductionmentioning
confidence: 94%
“…Based on this gap in the literature, the aim of the study is to examine the relationship between GMO and environmental and social performance of the firm in the context of the hospitality sector. This study is significant as the tourism industry is slowly changing priorities from pure economic considerations to a sustainable tourism marketing model (Aimagambetov, et al, 2017;Kisi, 2019). This study will make an empirical contribution to the literature on the nexus between GMO and environmental and social performance in the context of the hospitality industry.…”
Section: Introductionmentioning
confidence: 94%
“…Most European countries, and beyond, have to see rural development as a chance to fight poverty, to ensure the sustainability [1,2] of the rural environment, so each industry is encouraged to find a solution for sustainability in its own field [3]. Sustainability puts its accent on values and principles, which have as their main purpose to guide actions, in a responsible and harmonious way, taking into consideration the environmental and societal consequences, as well as economic purposes [4].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the notion "sustainable" is used in various fields, agritourism being one, so sustainability has become one of the most important strategic issues for many rural areas. [3] Most studies have shown that tourism combined with rural resources and traditional products would be an important "tool" for revitalizing rural, mountainous areas [16][17][18][19][20][21][22]. Modern patterns of rural development highlight that a rational and planned exploitation of agricultural resources together with the valorization of cultural and naturalistic heritage of rural areas, or simply said, the right leverage to assure sustainable growth of rural settlements, are through agritourism [23].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the seminal works by [28,29], a significant strand of literature developed and the number of its applications to real-world decision problems increased significantly [32][33][34]. The applications of the A'WOT method are varied and cover as major fields natural resource management [32,[35][36][37], sustainable tourism and tourism management [25,34,38,39], strategic assessment and group decision making (see among others, [40][41][42][43]). Although in the field of cultural heritage assessment, there are a flourishing set of recent contributions in literature on the sole application of AHP [44][45][46][47][48][49][50][51] and SWOT analysis [52][53][54][55][56], respectively.…”
Section: Description Of the Case Study: The Ducal Farmhouses In Agliémentioning
confidence: 99%